Correlation between Thrombopoietin Serum Level and Liver Fibrosis in Chronic Hepatitis Patients - Juwita Sembiring (The Indonesian Society for Digestive Endoscopy, 2010)
Background: Thrombopoetin (TPO) is a cytokine mainly produced in the liver and is the principal regulator in the humoral control mechanism of thrombopoesis. Presumably TPO production is not adequate in patients suffering from severe necroinflammation and advanced liver fibrosis in chronic hepatitis. The aim of this study was to identify the correlation between serum TPO levels and the degree of liver fibrosis. Method: With analytical cross-sectional design, this sudy analyzed the relationship between the serum TPO level and the degree of liver fibrosis in 62 chronic hepatitis patients from June 2006 to March 2008. The serum level of TPO was examined using the Quantikine human TPO immunoassay, and liver biopsy was performed in accordance to the Metavir scoring system. Results: There were 22 female and 33 male, with age range from 18 to 70 years old. We found that serum TPO levels were negatively correlated with the degree of liver fibrosis in a very significant fashion (r = -0.284, p 0.05). At serum TPO level 16.01 pg/mL or lower, the sensitivity and specificity of serum TPO for diagnosing the severity of the fibrosis were the 64.1% and 70.3% respectively, when the disease process was at F3 or greater level (p = 0.003). There was a significant difference between the degree of liver fibrosis and platelet count (p 0.0001), and significant negative correlation between the degrees of fibrosis with platelet level (r = - 0.783; p = 0.001). Conclusion: There was a significant negative correlation between serum TPO levels and the degree of liver fibrosis in chronic hepatitis patients and significant negative correlation between the degree of liver fibrosis and platelet count. Keywords: chronic hepatitis, liver fibrosis, thrombopoietin